Simmel, Love and the Foreigner: Is Love Between Borders a Love Without Limits? - Zanini, Maria; Kessler, Cláudia (Simmel Studies)

(untitled) (Edizioni ETS, 2021)
In this article, we reflect on the importance of the work of the German sociologist and philosopher Georg Simmel (1858-1918). We focus on reflections about love in certain mobility processes. Starting from a theoretical discussion about love in the Simmelian work, we unfold it to think about love in contexts of broader mobility. The Simmelian love, therefore, serves as an analytical basis that articulates the experiences of people in different geographical areas. Starting from the idea of frontier and limitation, we situate this analytical reflection in the contemporary pandemic context, when mobility and the lack of it also became more complex. Reflecting on love, in the midst of this sanitary crisis context, this discussion becomes extremely necessary and, in this aspect, Simmel proves to be a revealing author when it comes to the existing possibilities. His work contributes to the understanding of certain processes of interaction and mobility. In addition, we aim to review the notion of foreigner developed by Simmel, and think, to what extent, it is applicable to understand the dynamics inherent in the crossings between love and mobility. In the scenario of contemporary affective relationships, it is emphasized how much Simmel’s work is still fertile to comprehend certain feelings, emotions and perspectives. In the transnational context, in which time and spaces are constantly resized through access to new information, communication technologies and possibilities for creating and maintaining diverse bonds, the Simmelian perspective can very much lead us to a better interpretive notion of love in a context of mobility and immobility.